Inotropic score and vasoactive inotropic score as predictors of outcomes in congenital diaphragmatic hernia: A single center retrospective study - Hari Gopal, Srirupa; Toy, Cynthia L.; Hanna, Morcos; Furtun, Betul Yilmaz; Hagan, Joseph L.; Nassr, Ahmed A.; Fernandes, Caraciolo J.; Keswani, Sundeep; Gowda, Sharada H. (Frontiers in Pediatrics, 2023)
Background: Neonates with congenital diaphragmatic hernia (CDH) have varying degrees of pulmonary hypoplasia, pulmonary hypertension (PH) and cardiac dysfunction. These neonates frequently require vasoactive support and are at high risk for mortality and morbidity, including prolonged ventilator support, need for extracorporeal membrane oxygenation (ECMO), prolonged length of stay, and need for tracheostomy. However, identifying which infants are at increased risk can be challenging. In this study, we sought to investigate the utility of the inotropic score (IS) and vasoactive inotropic score (VIS) as tools to predict significant clinical outcomes and overall survival in patients with CDH. Additionally, we evaluated the correlation between IS/VIS and postnatal echocardiographic variables. Methods: This was a retrospective chart review of 57 patients with CDH. We calculated the IS/VIS at 6-, 12-, 24-, 48- hours of life (HOL), on the day of CDH repair and 24- and 48- hours after surgical repair. The association of these scores with postnatal echocardiographic markers was analyzed using linear regression, while logistic regression was used for binary outcomes, and Cox proportional hazards regression was used to assess associations with survival. Results: We found that every one-unit increase in IS/VIS at 6 HOL was associated with 13% increase in the odds of needing ECMO (p=0.034) and 10.1% increase in risk of death (p=0.021). An increase in IS/VIS at 12-, 24- and 48- HOL was associated with posterior septal bowing in first postnatal echocardiogram (p<0.05 for all). Additionally, we noted an inverse relationship between IS (p=0.036) and VIS (p=0.031) on the day of repair and left ventricle (LV) systolic function in first postnatal echocardiogram. Increase in IS (p=0.024) and VIS (p=0.037) on the day of repair was associated with decreased LV function on the post-repair echocardiogram. Conclusion: This retrospective study showed a significant association between IS/VIS obtained at various time points with clinical outcomes and echocardiographic findings in CDH and could be used to guide prognosis and management in this patient population.